Biological activities of Viscum tuberculatum aqueous leaf extract. (31st December 2023) - Yirgu, Abraham; Mekonnen, Yalemtsehay; Eyado, Amelework; Staropoli, Alessia; Vinale, Francesco
Abstract: Content: Plant-based natural products have served as sources of remedies against pathogenic microorganisms. Although the biological activities of Viscum (Santalaceae) species are widely recognized, there is no scientific evidence for Viscum tuberculatum A. Rich. in Ethiopia. Objective: To investigate the antimicrobial, acute toxicity, anti-inflammatory properties and phytochemical constituents of an aqueous extract of V. tuberculatum from Ethiopia. Materials and methods: The antibacterial activity of the aqueous leaf extract of V. tuberculatum was tested against Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus. The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of this extract were determined using the broth macrodilution method. The acute toxicity and anti-inflammatory effects of the extract were investigated using standard procedures on female and male white albino mice, aged 8 and 10 weeks, respectively. The phytochemical constituents of V. tuberculatum were determined using LC–MS QTOF. Results: The MIC and MBC values against S. aureus were found to be 6.25 and 100 mg/mL. The LD50 value was more than 2000 mg/kg body weight of the mouse. The 400 mg/kg dose exerts 87% inhibition after 5 h of carrageenan injection. Twenty-five different metabolites, mainly flavonoids, phenolic acids and alkaloids, were identified. Conclusions: These findings demonstrate the potential antimicrobial and anti-inflammatory potential of the aqueous extract of V. tuberculatum .